(3CfhGQ GdYbhd ef CTYGQ hMi GdQShds - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s ((3GdeHjf Hf fhQ GdOjf eMeO fGUQ GdOjf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi cGfJ dZQJg GdLHGHQI hHYO abO JMbb Cf GdYde CfaS eG jJfGaS ajg CfaS GdYGbdjf s
(3BNQgG (B:s
(3NjQ GdOhGhjf JMhjg hJMaXg ajg GdeYGdi hajg GdaVd eLJeYkG OjhGf TYQ CejQ GdeDefjf Ydi caVG UGMHg ai GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs